PENGARUH INTELLECTUAL CAPITAL TERHADAP PROFITABILITAS PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2013−2015) - B1031131023, CINDY CLAUDIA SUSANTO (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
The purpose of this study is to investigate the influence of Value Added Intellectual Coefficient indicated by the major components of a firm’s resource base (physical capital, human capital, and structural capital) towards firm’s profitability and market value that indicated by Basic Earning Ratio, Return on Equity, and Price Earning Ratio. Data were drawn from 31 listed manufacturing companies in Indonesian Stock Exchange during 2013-2015. The manufacturing companies is an unique industry, because this sector has high dependency on the intellectuality of its human resources. Using regression analysis, this study shows that the association between the Value Added Intellectual Coefficient and Basic Earning Power also Return on Equity are generally positive and significant. In contrast, the insignificant influence of value added intellectual coefficient is found its relationship to Price Earning Ratio. Keywords: Intellectual Capital, Value Added Intellectual Coefficient, Basic Earning Power, Return On Equity, Price Earning Ratio